2018
DOI: 10.5194/essd-10-317-2018
|View full text |Cite
|
Sign up to set email alerts
|

Surface and top-of-atmosphere radiative feedback kernels for CESM-CAM5

Abstract: Abstract. Radiative kernels at the top of the atmosphere are useful for decomposing changes in atmospheric radiative fluxes due to feedbacks from atmosphere and surface temperature, water vapor, and surface albedo. Here we describe and validate radiative kernels calculated with the large-ensemble version of CAM5, CESM1.1.2, at the top of the atmosphere and the surface. Estimates of the radiative forcing from greenhouse gases and aerosols in RCP8.5 in the CESM large-ensemble simulations are also diagnosed. As a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
164
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 123 publications
(169 citation statements)
references
References 16 publications
(22 reference statements)
5
164
0
Order By: Relevance
“…The magnitudes of LR and albedo feedbacks are comparable, but the LR feedback is the largest contributor to AA among these feedbacks, followed by the albedo feedback and Planck feedback deviation according to their distance to the 1:1 line. This ranking is the same as the results derived from the CESM large‐ensemble simulations (purple symbols in Figure a) in Pendergrass et al () and the CMIP5 multimodel ensemble mean in Pithan and Mauritsen (). The sign of LW cloud feedback over the Arctic is positive and consistent among three cases (Figure S3g), but the sign for SW cloud feedback is uncertain.…”
Section: Resultssupporting
confidence: 78%
See 2 more Smart Citations
“…The magnitudes of LR and albedo feedbacks are comparable, but the LR feedback is the largest contributor to AA among these feedbacks, followed by the albedo feedback and Planck feedback deviation according to their distance to the 1:1 line. This ranking is the same as the results derived from the CESM large‐ensemble simulations (purple symbols in Figure a) in Pendergrass et al () and the CMIP5 multimodel ensemble mean in Pithan and Mauritsen (). The sign of LW cloud feedback over the Arctic is positive and consistent among three cases (Figure S3g), but the sign for SW cloud feedback is uncertain.…”
Section: Resultssupporting
confidence: 78%
“…After that, the TOA flux anomalies are regressed onto the SAT anomalies to obtain the linear regression coefficient. According to the definition Δ R = Δ Q + λ Δ T s , we need to further deduct the Δ Q /Δ T s based on this regression coefficient to obtain the total feedbacks, where the Δ Q /Δ T s is calculated from relevant data in Pendergrass et al () and shown in the Table S1.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…They did, however, find significant differences between each year of the observational‐based water vapor kernel and the water vapor kernel developed using the National Center for Atmospheric Research (NCAR) CAM3 model (Shell et al, ), suggesting that interannual variability does not explain a significant portion of the differences between the observational and model‐derived radiative kernels. Similarly, Pendergrass et al () demonstrated that radiative kernels derived from a single year and single member of the CESM Large Ensemble (Kay et al, ) diagnose total flux changes with similar accuracy across all ensemble members, indicating that radiative kernel interannual variability is a relatively small source radiative kernel error.…”
Section: Methodsmentioning
confidence: 91%
“…To quantify the radiative forcing of anthropogenic aerosols, we apply satellite estimates of DRE to derive aerosol radiative kernels (Kramer et al, ; Soden et al, ). Radiative kernels are useful tools for evaluating radiative feedbacks in response to changes in aerosols (Gettelman et al, ; Pendergrass et al, ). Until now, however, observation‐based aerosol radiative kernels have not been published.…”
Section: Methodsmentioning
confidence: 99%